Um estudo sobre o uso de técnicas não-tradicionais aplicadas à detecção de defeitos de fabricação em câmbios automotivos - Pena, José Luiz Oliveira (2003)
In this work a study about the use of four mathematical-computational nontraditional tools with detection purpose and automatic classification of assembly and manufacturing defects in automotive gearboxes from vibration signals is presented. Due to the State of the gear meshing to be characterized by amplitude and phase modulations, two demodulation techiniques are considered. The demodulation of the amplitude and phase of the gear meshing signals using least squares and decomposition by Generalized S Transform, in the wich are used Windows that are adjusted to the characteristics of signafs modulation. The other two approaches, take into account the amplitude of the gear meshing frequencies and their lateral bands. In one, statistical tools, as kurtosis, crest factor and root mean square levei are adopted, applied to the time parcels associated to the frequencies of interest of Choi-Williams Transforms of the signals, and in another one is calculated the sum of the global Bispectrum magnitudes and also the sum of bispectrum related to the gear meshing frequency only. The proposed methodologies were applied to the simulated gear meshing vibration data, where a peliminary study is made for to evaluate the viability of each one. The chosen methodologies - Amplitude and phase demodulation and the one that uses Choi-Williams Transform were submitted to sensitivity analysis with simulated gear meshing signals in order to evaluate their capabilities how much to the modulation degree present in the signals, under several conditions of noise. Finaly, these two approaches were applied to the real vibration signals obtained of an automotive transmission.